The capacity of Islamic senior high school students to comprehend mathematical ideas and solve matrix problems - Handayani, Ucik Fitri; Anggraini, Lailatul (Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2023)
Kemampuan pemahaman konsep dalam mata pelajaran matematika sangat diperlukan oleh setiap siswa. Tujuan penelitian ini untuk mendeskripsikan kemampuan pemahaman konsep matematis siswa MA dalam menyelesaikan soal matriks. Penelitian dilaksanakan pada 53 siswa kelas XI di MA Mambaul Ulum Banjarejo. Teknik pengumpulan data yang digunakan adalah tes dan wawancara. Hasil penelitian yakni Kemampuan pemahaman konsep matematis siswa dalam setiap indikator berbeda-beda. Persentase indikator kemampuan pemahaman konsep siswa pada indikator ke-1 yakni 72%, indikator ke-2 yakni 93%, indikator ke-3 yakni 83%, indikator ke-4 yakni 88%, indikator ke-5 yakni 60%, indikator ke-6 yakni 55% dan indikator ke-7 yakni 60%. Persentase indikator kemampuan pemahaman konsep matematis siswa yang paling tinggi adalah merepresentasikan suatu konsep dalam berbagai bentuk matematis. Sedangkan, persentase indikator kemampuan pemahaman konsep siswa yang paling rendah yakni menerapkan prosedur atau operasi matematika dalam menyelesaikan soal. Guru dalam proses pembelajaran disarankan untuk tidak hanya menekankan pada hafalan, akan tetapi pada pemahaman konsep siswa. The ability to understand concepts in mathematics is needed by every student. The purpose of this study was to describe the ability to understand mathematical concepts of MA students in solving matrix problems. The research was conducted on 53 students of class XI at MA Mambaul Ulum Banjarejo. Data collection techniques used were tests and interviews. The results of the research are the ability to understand students' mathematical concepts in each indicator is different. The percentage of students' concept understanding ability indicators on the 1st indicator is 72%, the 2nd indicator is 93%, the 3rd indicator is 83%, the 4th indicator is 88%, the 5th indicator is 60%, the 3rd indicator 6 is 55% and the 7th indicator is 60%. The highest percentage of student's ability to understand mathematical concepts is representing a concept in various mathematical forms. Meanwhile, the lowest percentage of students' concept comprehension indicators is applying mathematical procedures or operations in solving problems. Teachers in the learning process are advised not only to emphasize memorization but also to understand students' concepts.